Association between steatotic liver disease and microvascular complications in individuals with type 2 diabetes: a cohort study in the UK Biobank - Liu, Longfu; You, Qiqi; Yu, Wenxiang; Lett, Aaron M.; Wu, Yucen; Zeng, Jingjing; Fan, Menglin; Chen, Bo; Fu, Wan; Xu, Shaoyong (Frontiers in Endocrinology, 2025)
BackgroundCross-sectional studies have revealed that steatotic liver disease (SLD) is associated with prevalent diabetic microvascular complications, but longitudinal evidence in large samples is insufficient. We aimed to prospectively investigate the association between SLDs and the risk of microvascular complications in patients with type 2 diabetes (T2D), and to explore whether glycemic control played a mediating role in this association.MethodsThe population-based cohort, which was based on the UK Biobank study, included 25,630 T2D patients at baseline. SLD was defined as a fatty liver index ≥ 60. A glycated hemoglobin level ≥ 7% (53 mmol/mol) was considered poor glycemic control. The primary outcome was total incident diabetic microvascular complications, defined as the first occurrence of diabetic nephropathy, diabetic neuropathy, and/or diabetic retinopathy. The cox proportional hazard regression model was used to calculate hazard ratios (HRs) and 95% confidence intervals (CIs) for diabetic microvascular complications. Mediation analysis was applied to explore whether the association between SLDs and diabetic microvascular complications was mediated by glycemic control.ResultsThe mean age of the study participants was 59.6 years, and 58.1% of them were males. During a median follow-up period of 12.1 years, 5,171 participants were diagnosed with microvascular complications. Compared with non-SLD participants, SLD participants had a HR of 1.15 (95% CI: 1.04, 1.27) for total microvascular complications, a HR of 1.20 (95% CI: 1.06, 1.35) for diabetic nephropathy, a HR of 1.05 (95% CI: 0.91, 1.21) for diabetic retinopathy, and a HR of 1.46 (95% CI: 1.15, 1.86) for diabetic neuropathy. The results of the mediation analysis revealed that the mediating proportion of glycemic control in the association between the SLD group and total diabetic microvascular complications was 22.5% (95% CI: 10.4%, 91.0%).ConclusionsSLD was associated with an increased risk of microvascular complications, especially diabetic nephropathy and diabetic neuropathy, in T2D patients. Glycemic control partially mediated the association between SLDs and diabetic microvascular complications.